(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
In Different Countries Of The World, The Parliament Has The Mission Of Legislation, And In Algeria, This Institution Has Evolved Through The Various Constitutions That The Algerian Republic Has Developed And The Capabilities Of This Institution Have Evolved Since The Era Of Unilateralism To The Era Of Multiparty. The Parliament Has Become More Dynamic Through A Series Of Amendments Defined By The 1996 Constitution, Especially The 2016 Amendments, Which Have Given The Legislature New Abilities. Key words - Parliament, legislation, political system, constitution, executive authority